Factors Influencing Hypoglycemia in Type 2 Diabetes Mellitus Outpatients with State Health Insurance at Regional General Hospitals in Jakarta, Indonesia - Veryanti, Putu Rika; Sauriasari, Rani; Sartika, Ratu Ayu Dewi; Elya, Berna (Current Diabetes Reviews, 2025)
BackgroundHypoglycemia is an acute episode that can lead to death in patients with diabetes mellitus (DM). This condition is preventable with patient education, and identifying factors influencing their occurrence is essential to creating effective and efficient education. It also leads to prevention and control by re-organizing the service system and diabetes policies. This study aimed to determine factors contributing to hypoglycemic episodes in type 2 DM outpatients covered by the state-provided Jaminan Kesehatan Nasional (JKN) health insurance.MethodsThe study used a cross-sectional design and collected data from five regional general hospitals in Jakarta, Indonesia. The outpatients were sampled consecutively from two hospitals in September–November 2021, one in January–March 2022, and two others in April–June 2023. Interviews produced primary data related to experienced hypoglycemic episodes, and medical records provided secondary data on patients' clinical characteristics and treatments. Binary logistic regression analysis was employed to process the contributing factors statistically.ResultsFrom 501 patients who met the inclusion and exclusion criteria, it was found that the prevalence of hypoglycemia was 53.3%. Factors that significantly increased hypoglycemic risk (p < 0.05) were high HbA1c levels (OR 1.9; 95% CI 1.2–2.9), comorbidities (OR 1.6; 95% CI 1.1–2.4), insulin/sulfonylurea therapy (OR 2; 95% CI 1–4), non-smoking habit (OR 2.2; 95% CI 1.3–3.6) and physically active lifestyle (OR 1.8; 95% CI 1.2–2.6).ConclusionThe prevalence of hypoglycemia in type 2 diabetes mellitus (DM) outpatients with the state-provided health insurance Jaminan Kesehatan Nasional (JKN) at general hospitals in Jakarta is high. The diabetes self-management education (DSME) services provided by health professionals for these outpatients must be further improved.
Keywords: Influencing factors